AI-Enabled Information Systems and Strategic Alignment: A Systematic Literature Review on Digital Orchestration - Budianto, Farhan Alif; Lubis, Muharman; Mukti, Iqbal Yulizar; Budianto, Setyo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This paper aims to synthesize the fragmented body of literature on how Artificial Intelligence (AI) transforms the traditional Strategic Alignment Model (SAM). Specifically, the study examines the role of Digital Orchestration as a mediating mechanism between AI capabilities and organizational performance. Using a Systematic Literature Review (SLR) approach guided by PRISMA protocols, this research analyzes 84 peer-reviewed articles published between 2018 and 2026 and indexed in the Scopus and Web of Science databases. The study identifies three main thematic pillars: Cognitive Alignment, Algorithmic Governance, and Human–AI Collaborative Synergy. Overall, these themes indicate that AI is no longer merely an operational support tool but has evolved into an agentic strategic capability that enables continuous sensing, predictive decision-making, and real-time synchronization between business and IT domains. The findings demonstrate a paradigm shift from “Static Fit” toward “Fluid Orchestration.” Theoretically, this study extends the Resource-Based View by positioning agentic AI capability as a higher-order dynamic capability and proposes an AI-Enabled Digital Orchestration Framework to integrate previously fragmented insights. Managerially, the research emphasizes the importance of Dynamic KPIs and Agentic Governance to prevent algorithmic misalignment. Overall, the study advances strategic alignment theory by framing AI-driven strategy as a continuously adaptive orchestration capability in volatile digital ecosystems.